THE EFFECT OF RECENT LAWS ON ACCOUNTANCY. - Payne, Robert E. (The Accounting Review, 1935)
Accounting is a young profession, but in recent years the public has come to realize that an accountant has some ability beyond that of keeping books. Its recent recognition in the various federal and state laws, stock-exchange regulations, and the Investment Bankers' code of fair competition should bring about a still greater recognition of the value of its service. The lawyer's interests are mainly those of his client, but the accountant is called upon to report to his client, his client's creditors and bankers, his client's security holders, and the public. The average audit report serves many purposes, and the accountant's responsibilities extend to all the readers of his report. Recent laws, which have given recognition to accountants include, the Securities Act of 1938 which deals with the registration of new securities for interstate sale, the Securities Exchange Act of 1934, which provides for the registration of listed securities, etc. These new laws with their drastic liabilities should certainly result in some improvement of work done, and thus will be of great benefit to reputable accounts.